Evaluation of the Expression of Genes Associated with Inflammation and Apoptosis in Androgenetic Alopecia by Targeted RNA-Seq - Martínez Jacobo, Lizeth Alejandra; Ancer Arellano, Claudia I.; Ortiz López, Rocío; Salinas Santander, Mauricio Andrés; Villarreal Villarreal, César Daniel; Ancer Rodríguez, Jesús; Camacho Zamora, Bianka Dianey; Zomosa Signoret, Viviana Chantal; Medina de la Garza, Carlos Eduardo; Ocampo Candiani, Jorge; Rojas Martínez, Augusto (2017)
Abstract Androgenetic alopecia (AGA) or male pattern baldness is the most common form of hair loss in humans. Despite being a very frequent dermatological entity, molecular pathophysiology remains unclear. Several authors relate the presentation of AGA with a premature apoptotic process during the anagen phase and with an inflammatory microenvironment in the hair follicle. We evaluated a panel of 30 genes associated with inflammation and apoptosis in 5 AGA patients by targeted RNA-Seq. WNT7A gene was highly expressed in patients in stages 3V to 5 on the Hamilton-Norwood scale compared to patients with 5A stage. CASP7 and TNF genes were overexpressed in stages 3V and 4 compared to stages 5 and 5A. Overexpression of these genes detected only at early stages of AGA proves the role of WNT pathway, apoptosis, and inflammation in the development of this disorder.